2020
DOI: 10.1159/000506118
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of High-Dose Tolvaptan for Autosomal Dominant Polycystic Kidney Disease Patients

Abstract: Tolvaptan, a vasopressin V2 receptor antagonist, was initially approved in Japan for treatment of autosomal dominant polycystic kidney disease (ADPKD). Recently, a retrospective study showed that the effect of tolvaptan on kidney function could be sustained for a long period. However, the long-term efficacy and safety of high-dose tolvaptan (120 mg/day) in individual cases remain unknown. We report here 2 Japanese ADPKD patients (males, 36 and 29 years old) treated with tolvaptan (120 mg/day) for 9 years, duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Tolvaptan should be given at 45 mg postoperative initially on waking and 15 mg taken 8 h later (i.e. 60 mg.day) [14]. A study also showed that long-term administration of tolvaptan at a high dose is both safe and effective to reserve kidney function, though a gradual increase in total kidney volume was seen, particularly during the later phase [15].…”
Section: Discussionmentioning
confidence: 99%
“…Tolvaptan should be given at 45 mg postoperative initially on waking and 15 mg taken 8 h later (i.e. 60 mg.day) [14]. A study also showed that long-term administration of tolvaptan at a high dose is both safe and effective to reserve kidney function, though a gradual increase in total kidney volume was seen, particularly during the later phase [15].…”
Section: Discussionmentioning
confidence: 99%